Design of an equivalent dielectric film using periodic patterned screen printing and prediction of dielectric constants based on equivalent circuit method. (1st September 2021) - Baek, Sang Min; Lee, Won Jun; Kim, Sang Yong; Kim, Seong Su
Abstract: This study proposed a method to control the electromagnetic (EM) properties of a material by controlling its pattern dimensions. A conductive paste, comprising graphite and carbon black, was printed on the surface of a high-heat resistant polyester film with rectangular patterns using screen printing. The EM parameters of the material were extracted using one-dimensional approximate equivalent circuit method and the dielectric constant of the material was predicted. The pattern width had a positive correlation with the EM parameters, including the dielectric constant. The equivalent dielectric constant changed with the substrate thickness and surface resistance, as obtained from the parametric study. EM wave absorbers were designed based on transmission line theory and fabricated by stacking the developed materials with various dielectric slab materials. The results of the measurement and simulation confirmed the effectivity of the EM absorber design using the proposed material.